Computational analysis of tibial slope adjustment with fixed-bearing medial unicompartmental knee arthroplasty in ACL- and PCL-deficient models - Hyuck M. Kwon; Jin-Ah Lee; Yong-Gon Koh; Kwan K. Park; Kyoung-Tak Kang (Bone & Joint Research, 2022)
Aims: A functional anterior cruciate ligament (ACL) or posterior cruciate ligament (PCL) has been assumed to be required for patients undergoing unicompartmental knee arthroplasty (UKA). However, this assumption has not been thoroughly tested. Therefore, this study aimed to assess the biomechanical effects exerted by cruciate ligament-deficient knees with medial UKAs regarding different posterior tibial slopes. Methods: ACL- or PCL-deficient models with posterior tibial slopes of 1°, 3°, 5°, 7°, and 9° were developed and compared to intact models. The kinematics and contact stresses on the tibiofemoral joint were evaluated under gait cycle loading conditions. Results: Anterior translation increased in ACL-deficient UKA cases compared with intact models. In contrast, posterior translation increased in PCL-deficient UKA cases compared with intact models. As the posterior tibial slope increased, anterior translation of ACL-deficient UKA increased significantly in the stance phase, and posterior translation of PCL-deficient UKA increased significantly in the swing phase. Furthermore, as the posterior tibial slope increased, contact stress on the other compartment increased in cruciate ligament-deficient UKAs compared with intact UKAs. Conclusion: Fixed-bearing medial UKA is a viable treatment option for patients with cruciate ligament deficiency, providing a less invasive procedure and allowing patient-specific kinematics to adjust posterior tibial slope. Patient selection is important, and while AP kinematics can be compensated for by posterior tibial slope adjustment, rotational stability is a prerequisite for this approach. ACL- or PCL-deficient UKA that adjusts the posterior tibial slope might be an alternative treatment option for a skilled surgeon. Cite this article: Bone Joint Res 2022;11(7):494–502.